SwiftUI Cookbook - Second Edition - Scalzo, Giordano; Nzokwe, Edgar (Packt Publishing, 2021)
Find practical, logical, and efficient recipes for building cross-platform apps for iOS 15, macOS, and watchOS using Swift 5.5, Xcode 13, and SwiftUI 3.0 Key Features Apply the declarative programming paradigm to build cross-platform UIs for Apple devices Learn to integrate UIkit, Core Data, Firebase, and Sign in with Apple with SwiftUI Adopt the new SwiftUI 3.0 features to build visually appealing UIs speedily Book Description SwiftUI provides an innovative and simple way to build beautiful user interfaces (UIs) for all Apple platforms, from iOS and macOS through to watchOS and tvOS, using the Swift programming language. In this recipe-based cookbook, you'll cover the foundations of SwiftUI as well as the new SwiftUI 3 features introduced in iOS 15 and explore a range of essential techniques and concepts that will help you through the development process. The cookbook begins by explaining how to use basic SwiftUI components. Once you've learned the core concepts of UI development, such as Views, Controls, Lists, and ScrollViews, using practical implementations in Swift, you'll advance to adding useful features to SwiftUI using drawings, built-in shapes, animations, and transitions. You'll understand how to integrate SwiftUI with exciting new components in the Apple development ecosystem, such as Combine for managing events and Core Data for managing app data. Finally, you'll write iOS, macOS, and watchOS apps by sharing the same SwiftUI codebase. By the end of this SwiftUI book, you'll have discovered a range of simple, direct solutions to common problems encountered when building SwiftUI apps. What you will learn Explore various layout presentations in SwiftUI such as HStack, VStack, LazyHStack, and LazyVGrid Create widgets to quickly display relevant content at glance Get up to speed with drawings in SwiftUI using built-in shapes, custom paths, and polygons Discover modern animation and transition techniques in SwiftUI Add user authentication using Firebase and Sign in with Apple Manage concurrency with Combine and async/await in SwiftUI Solve the most common SwiftUI problems, such as integrating a MapKit map, unit testing, snapshot testing, and previewing layouts Who this book is for This book is for mobile developers who want to learn SwiftUI as well as experienced iOS developers transitioning from UIkit to SwiftUI. The book assumes knowledge of the Swift programming language. Knowledge of object-oriented design and data structures will b ...